Effect of cancer-associated fibroblasts on the migration of glioma cells in vitro - Trylcova, Jana; Busek, Petr; Smetana, Karel; Balaziova, Eva; Dvorankova, Barbora; Mifkova, Alzbeta; Sedo, Aleksi (Tumour biology, 2015)
Cancer-associated fibroblasts (CAFs) significantly influence biological properties of many tumors. The role of these mesenchymal cells is also anticipated in human gliomas. To evaluate the putative role of CAFs in glioblastoma, we tested the effect of CAF conditioned media on the proliferation and chemotaxis of glioma cells. The proliferation of glioma cells was stimulated to similar extent by both the normal fibroblasts (NFs) and CAF-conditioned media. Nevertheless, CAF-conditioned media enhanced the chemotactic migration of glioma cells significantly more potently than the media from normal fibroblasts. In order to determine whether CAF-like cells are present in human glioblastomas, immunofluorescence staining was performed on tissue samples from 20 patients using markers typical for CAFs. This analysis revealed regular presence of mesenchymal cells expressing characteristic CAF markers α-smooth muscle actin and TE-7 in human glioblastomas. These observations indicate the potential role of CAF-like cells in glioblastoma biology.
Keywords: regulace genové exprese u nádorů; proliferace buněk; Cell Line, Tumor; kultivační média speciální; Fibroblasts; Gene Expression Regulation, Neoplastic; nádorové mikroprostředí; lidé; Culture Media, Conditioned; fibroblasty; glioblastom; Glioblastoma; pohyb buněk; aktiny; Actins; Cell Proliferation; Tumor Microenvironment; Cell Movement; nádorové buněčné linie; Humans